Experimental poisoning by Pseudocalymma elegans in rabbits and guinea-pigs - Tavares, Maria Ivone; Rezende, Ana Margarida L. de; Döbereiner, Jürgen (Pesquisa Agropecuaria Brasileira, 2014)
The toxicity of Pseudocalymma elegans, a plant poisonous to cattle, was investigated using laboratory animals. Eight rabbits were dosed, by stomach tube, with 0.30 and 0.33 g/kg of dried leaves. Two guinea-pigs received 6.0 and 7.7 ml/kg of fresh leaf extract and six others aqueous extracts from dried leaves that corresponded with 0.3 to 2.0 g/kg of the dry plant material. Freshly collected and the dried leaves were toxic to the rabbits and the guinea-pigs. Seven rabbits died between 1 hour and 38 minutes and 7 hours and 7 minutes after administration. Seven guinea-pigs died between 3 hours and 10 minutes to approximately 29 hours after the initiation of the experiment. Post-mortem examinations and histopathological changes indicated haemorrhages in the lungs and hydropic-vacuolar degeneration of liver cells. The dried plant material remained toxic for six years after its collection.